FEATURES OF THE FUNCTIONING OF THE BRICS GROUP AS AN INFORMAL INTERNATIONAL ASSOCIATION - N. Sekongo; V. Antonov; T. Titus (Вестник университета)
The article examines some indicators that characterize the role of BRICS in the global economic system. It is shown that in the modern global world these countries have many common features. Particular attention is paid to the prospects for the development of the BRICS group due to the expansion of the number of participants. The authors of the article assume the further strengthening of the role of BRICS due to the growth of the economy of China and other countries.